Changes in the epidemiological profile of poisonings during COVID-19: differences between the first half of 2019 and 2020 - Pereska, Zanina; Bekjarovski, Niko; Simonovska, Natasha; Babulovska, Aleksandra; Naumoski, Kiril; Kostadinoski, Kristin (My University, 2021)
Objective: The COVID-19 pandemic has changed the epidemio- logical profile of acute poisonings, due to social changes related to preventive measures for protection against SARS-CoV-2 [1]. The purpose of this analysis is to compare the changes in the epidemiological characteristics of acute poisonings between the first half of 2019 and 2020. Methods: A retrospective study analyzing the data from the Register for poisonings, of the Poison Information Center, University Clinic of Toxicology, Skopje, Macedonia. Results: During the first half of 2020, a total of 564 cases of acute poisoning were registered presenting a decrease of 23.7% compared to the same period in 2019. The monthly percentage distribution of patients in the first half of 2020 showed more patients in January and February, and a decrease in the remain- ing 4 months, which coincided with the onset of the COVID-19 pandemic. The lowest prevalence was registered in March and April with a percentage decrease (23.6% and 24.1%, respectively), when quarantine measures were introduced in Macedonia. Although there was no significant difference in out/inpatient treatment groups between 2019 and 2020 year (X2 ¼0.605, df ¼1, P ¼0.437), in April 2020, during quarantine, the percentage difference between inpatients and outpatients was the lowest (6%) of all months in 2019 and 2020. The distribution of poison- ings by motive (suicidal, abuse and accidental) did not differ sig- nificantly between the first half of the last 2 years (X2 ¼0.178, df ¼2, P ¼0.915). The percentage of ethanol abuse, medicines and mushroom poisoning cases was reduced in 2020 compared to 2019 by 2.2%, 7.4% and 79.3%, respectively. In contrast, psycho- active substance cases increased by 51.5% in the first half of 2020 compared to the first half of 2019. In the group of recre- ational drug abuse cases, the largest increase was observed in heroin (141.2%) and methadone (125.1%) overdose. For chemi- cals, there was a large increase in cases involving disinfectants (681.0%) in 2020. There was no change in the case fatality ratio of total (1.8%) and hospitalized patients (4.8%) between 2019 and 2020. Conclusion: The first half of 2020 compared to the same period in 2019 was characterized by an increase in poisonings with dis- infectants and psychoactive substances. he decrease in the total number of poisonings, with the largest decrease in the quaran- tine months, stress the need to examine family dynamics and communication as a social key to reducing the number of poisonings.